Identity claims, texts, Rome and Galatians - Jeremy Punt (Acta Theologica)
This contribution explores the interplay between Paul’s use of the Scriptures of Israel and the imperial setting in claims about Abraham and the negotiation of identity in the Galatians letter. The letter, from Paul’s perspective, is testimony to fierce contestation of identity and finds him engaged in describing, defining and scripting insiders and outsiders in and around the community. In his efforts to argue for a certain identity, Paul not only enlisted the Scriptures of Israel but also availed himself of frameworks reminiscent of contemporary socio-political notions, and of imperial posturing in particular.